THE IMPLEMENTATION OF PROJECT-BASED LEARNING THAT UTILIZES SHAPE POEM TECHNIQUE IN TEACHING VOCABULARY IN ELEMENTARY SCHOOL - Dewi, Ida Ayu Komang Trisna; Padmadewi, Ni Nyoman; Artini, Luh Putu (Universitas Suryakancana, 2024)
In the 21st century, the evolving educational landscape demands innovative approaches to foster skills beyond mere understanding. Project-based learning, emphasizing authentic experiences and the development of 6C skills, emerges as a fitting model. This study explores the impact and teachers’ perception of project-based learning by utilizing the shape poem technique on vocabulary mastery among fifth-grade students at SD Laboraturium Undiksha Singaraja, a school aspiring to bilingual status.Theoretical frameworks draw on the aesthetic appreciation of poem, emphasizing its visual representation. Insights from various studies underscore the effectiveness of project-based learning in improving academic achievement and attitudes, particularly in language acquisition. The shape poem technique, a subset of concrete poetry, aligns with young learners' preferences for creative and enjoyable approaches.The research methodology employs a mixed-method design involving quantitative assessments and qualitative insights. Statistical analyses reveal significant improvements in vocabulary mastery through pre-and post-tests, supporting the efficacy of project-based learning with the shape poem technique. Teachers' perspectives, as elucidated through questionnaires and interviews, emphasize the positive impact on students' vocabulary mastery. They express confidence in its suitability for young learners, fostering motivation, creativity, and real-world language application. The teachers envision sustained benefits and anticipate continued application in the future, reinforcing the belief that students will experience lasting growth and development through enjoyable, authentic, and meaningful learning.In conclusion, the implementation of project-based learning by utilizing shape poem technique proves to significantly enhance students' vocabulary mastery. Teachers' perceptions affirm its effectiveness and potential for future applications, heralding a positive shift in language education paradigms